Impacts of plantation forest management on soil organic matter quality - Huang, Zhiqun; Clinton, Peter W.; Davis, Murray R.; Yang, Yusheng (Journal of soils and sediments, 2011)
Purpose Light fraction soil organic matter is characterized by rapid mineralization due to the labile nature of its chemical constituents and to the lack of protection by soil colloids. The changes in the size of light fraction soil organic matter constituents are useful early indicators of management-related carbon (C) and nutrient changes. However, previous studies have not assessed the impacts of forest management practices on the chemical composition and sources of organic matter in the light fraction. The change in the chemistry of light fraction soil organic matter may significantly affect turnover rate of organic matter in the whole soil and soil fertility. The aim of this study was to assess how different forest management practices would affect the chemical composition of light fraction soil organic matter. Materials and methods Soils in 0–5, 5–15, and 15–25-cm layers were sampled in 2009 from a 19-year-old second-rotation Pinus radiata D. Don plantation. Soils were subject to four different treatment combinations (stem-only and whole-tree harvesting residue management treatments were combined with the presence or absence of nitrogen (N)). The soil was physically separated into two pools based on density fractionation. The C and N concentrations in the whole soil, light, and heavy fractions were determined. Light fraction soil organic matter in upper soil (0–5 cm depth) was analyzed by solid-state CPMAS 13 C NMR and GC/MS to determine the effects of forest management practices on the composition of organic C functional groups and the relative abundance of plant biomarkers. Results and discussion Long-term fertilization did not affect the C and N concentrations in the whole soil, light and heavy fractions, but increased the relative enrichment of alkyl C and alkyl-to-O-alkyl C ratio in the light fraction soil organic matter at the 0–5 cm depth, which may suggest increased decomposition of the light fraction. The relative abundance of cutin-derived compounds, which originate from the waxy coating of leaves, was greater in the light fraction soil organic matter in the fertilized plots than in the unfertilized plots. The relative abundance of major carbohydrates, labile components in the light fraction soil organic matter, decreased in the fertilized plots despite greater inputs from forest litter, compared to that in the unfertilized plots. Compared with whole-tree harvest plots, stem-only harvest plots had greater C concentrations in the light fraction soil organic matter at 0 to 25-cm layer and seemed to have a greater alkyl-to-O-alkyl ratio in the light fraction of soil organic matter, but the difference in alkyl-to-O-alkyl ratio due to harvest residue management was not significant ( P < 0.05) at the 0–5 cm depth. Post-harvesting residue management did not significantly affect functional organic C groups as analyzed by CPMAS 13 C NMR, or the relative abundance of cutin, suberin, lignin-derived compounds or major carbohydrates determined by GC/MS. Conclusions The analyses of light fraction soil organic matter suggest that long-term fertilization did not affect the C concentration of light fraction soil organic matter, but increased the relative enrichment of recalcitrant C possibly due to enhanced input of cutin-derived compounds, decreased decomposition of cutin-derived compounds, or increased decomposition of less recalcitrant compounds. Stem-only harvesting residue management enhanced C concentration in the light fraction soil organic matter; however, it did not significantly affect the relative abundance of recalcitrant or labile C components compared to whole-tree harvesting. The information on chemistry of light fraction soil organic matter may contribute to the future nutrient and soil C management in the second-rotation plantation.